Optimization of Process Parameters in Friction Stir Welding of Aluminum 5451 in Marine Applications - Shoaib Ahmed; Rana Atta ur Rahman; Awais Awan; Sajjad Ahmad; Waseem Akram; Muhammad Amjad; Mohd Yazid Yahya; Seyed Saeid Rahimian Koloor (Journal of Marine Science and Engineering, 2022)
Friction stir welding (FSW) is one of the primary fabrication techniques for joining different components, and it has become popular, especially in aluminum alloy structures for marine applications. The welded joint with the friction stir process greatly depends on the process parameters, i.e., feed rate, rotational speed, and pin profile of the tool. In the current study, plates of aluminum 5451 alloy were joined by the FSW technique, and the Taguchi method was used to find the process parameters at an optimal level. The maximum value of tensile strength, i.e., 160.6907 MPa, was achieved using optimum welding conditions of a tool rotation speed of 1400, a feed rate of 18 mm/min, and the tool pin with threads. The maximum value of hardness, i.e., 81.056 HV, was achieved using optimum conditions of 1200 tool rotational speed and a feed rate of 18 mm/min with a tool pin profile having threads. In addition, the contribution in terms of the percentage of each input parameter was found by the analysis of variance (ANOVA). The ANOVA results revealed that the pin profile of the tool has the maximum contribution of 67.77% and 62.42% in achieving the optimum value of tensile strength and hardness, respectively. The study also investigated the joint efficiency of the friction stir welded joint, hardness at the weld zone, and metallography on FSW samples at the optimized level. The effectiveness and reliability of FSW joints for shipping industry applications can be observed by joint efficiency. That was investigated at optimum conditions, and it comes out to be 80.5%.